Evaluation of Serum Apolipoprotein A1 in Canine Sepsis - Giunti, Massimo; Grossi, Giorgio; Troía, Roberta; Fracassi, Federico; Dondi, Francesco (Frontiers in Veterinary Science, 2020)
Decreased serum apolipoprotein A1 (Apo-A1) concentration is associated with mortality in human sepsis. The diagnostic and prognostic role of serum Apo-A1 concentrations in canine sepsis was evaluated. Serum samples from septic dogs (n=91) and healthy controls (n=15) were retrospectively analyzed. According to the sepsis origin, four categories were identified: parvoviral enteritis (n=26), pyometra (n=20), septic peritonitis (n=19) and miscellanea (n=26). The canine acute patient physiologic and laboratory evaluation fast score (APPLEfast), serum C-reactive protein (CRP) and albumin concentrations were reviewed in all enrolled dogs. Increased CRP (252.6 ± 119.2 mg/L; Reference Interval: 0-8.5 mg/L) and significant lower serum albumin and Apo-A1 concentrations were documented in dogs with sepsis (22.8 ± 5.3 g/L and 1.17 ± 0.27 g/L, respectively) compared to healthy ones (33.1 ± 2.5 g/L and 1.32 ± 0.05 g/L, respectively) (P<0.0001). According to the origin of sepsis, only the subgroup of dogs with septic peritonitis had significantly lower Apo-A1 (1.03 ± 0.26 g/L) concentrations compared to healthy dogs (P<0.001). No significant differences were found in serum albumin and CRP concentrations, and in APPLEfast score values among the different subgroups of sepsis. Diagnosis of septic peritonitis was associated with a higher frequency of death (P= 0.006). In septic dogs, significant lower Apo-A1 concentrations were detected in non survivors (1.02 ± 0.28 g/L; n=27) compared to survivors (1.23 ± 0.24 g/L; n=64) (P=0.0007). Moreover, significant higher values of the APPLEfast score were calculated in non survivors (26 ± 4; n=19) compared to survivors (23 ± 4; n=51) (P=0.0114). According to the area under the ROC curve analysis, Apo-A1<96 mg/dl had a fair accuracy (AUC = 0.72) to correctly predict mortality (P=0.0004). Apo-A1 might support a diagnosis of canine septic peritonitis with a potential prognostic significance. Further prospective studies are warranted.